Cross-cultural studies of important ethno-medicinal plants among four ethnic groups of Arunachal Pradesh, Northeast India - Siram, Jopi; Hedge, Nagaraj; Singh, Rambir; Sahoo, Uttam Kumar (Ethnobotany Research and Applications, 2023)
Background: This study was carried out to measure cross-cultural variability of plant use knowledge and to understand the human-nature interface among Monpa, Miji, Aka and Bugun communities of district West Kameng, Arunachal Pradesh, India. We compared ethnomedical knowledge, diversity of medicinal plants, use values and informant consensus in the selected ethnic societies. Methods: A total of 94 informants (53 men and 41 women) from 02 villages of each community agreed to participate in this cross-cultural ethnomedicinal study. They were interviewed using a semi structured questionnaire and asked about the medicinal plants used for the management of prevalent ailments, mode of preparation and administration of traditionally prepared medicine. Results: Total 59 plant species from 52 genera and 43 families were recorded for their ethnomedicinal use by the selected communities. Zingiberaceae was the most common family with 03 genera and 05 spp., having high recommended use across the ethnic communities. Curcuma amada (1.85), Curcuma longa (1.60), Zingiber officinalis (1.48) of this family showed high cross-cultural use value as compared to other medicinal plants. The informant consensus factor for use of medicinal plants for management of cancer was high (0.99) indicating high prevalence of this ailment in this study area, availability and use of similar plants for its management. Conclusions: The high consensus for plants used in management of most of the prevalent ailments indicate good cross-cultural interaction among Monpa, Miji, Aka and Bugun communities of district West Kameng, Arunachal Pradesh, India. The medicinal plants with high use value and consensus need to be conserved and propagated for their sustained availability to the future generations. Keywords: Monpa, Miji, Aka, Bugun, Medicinal plants, Intercultural